DYSTOCIA DUE TO HYDROCEPHALUS FOETUS WITH EXTENSIVE MULTIPLE PHYSICAL DEFORMITY IN A CROSSBRED COW - POTHIAPPAN, p; KUMAR, R SURESH; KUMAR DAS, ANANGA; KUMAR, S SELVA; ARUN, A; CHANDRASEKARAN, D; BALASUBRAMANIAN, S (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to hydrocephalus foetus with extensive multiple physical deformity in a crossbred cow was reported.